2020
DOI: 10.1177/1362361319900422
|View full text |Cite
|
Sign up to set email alerts
|

Sluggish cognitive tempo: An examination of clinical correlates for adults with autism

Abstract: Adults with autism spectrum disorder often experience co-occurring mental health problems such as attention-deficit/hyperactivity-disorder, as well as impairments in executive function. Sluggish cognitive tempo, a cluster of behaviors including slow processing, daydreaming, and mental fogginess, has been shown to be associated with attention-deficit/hyperactivity-disorder. This study was designed to assess sluggish cognitive tempo in young adults with autism spectrum disorder. Specifically, we sought to establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 46 publications
3
8
1
Order By: Relevance
“…In contrast, a more recent study in adults with ASD reported that co-occurring SCT may not pose a heightened risk for anxiety symptoms. 8 Temperamental traits of certain anxiety dimensions may also shed light on the link between SCT and anxiety. For instance, social anxiety is usually accompanied by marked behavioral inhibition, and said inhibition may partly explain the SCT characteristics of hypoactivity and lower engagement in social situations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, a more recent study in adults with ASD reported that co-occurring SCT may not pose a heightened risk for anxiety symptoms. 8 Temperamental traits of certain anxiety dimensions may also shed light on the link between SCT and anxiety. For instance, social anxiety is usually accompanied by marked behavioral inhibition, and said inhibition may partly explain the SCT characteristics of hypoactivity and lower engagement in social situations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a more recent study in adults with ASD reported that co-occurring SCT may not pose a heightened risk for anxiety symptoms. 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between ASD and SCT was first examined in a current study and SCT symptoms were found to be significantly higher in adolescent cases with ASD (24). An up-to-date study in young adults with ASD found that one-third of these cases had high levels of SCT symptoms (25). The coexistence of these two psychopathologies may be associated with a possible similarity or overlap between their symptoms.…”
Section: Differential Diagnostic Process In the Case With Sctmentioning
confidence: 72%
“…A study found SCT symptoms to be significantly higher in adolescent cases with ASD 24 . An up‐to‐date study in young adults with ASD found that one‐third of these cases had high levels of SCT symptoms 25 . The coexistence of these two psychopathologies may be associated with a possible similarity or overlap between SCT and ASD symptoms.…”
Section: Discussionmentioning
confidence: 99%